Structural and Functional Responses of Small Mammal Communities to Land Abandonment in a Region of High Biodiversity - Anamaria Lazăr; Marcela Alexandra Sandu; Ana Maria Benedek; Ioan Sîrbu (Animals)
Small mammals are common in farmland, where their communities are affected by agricultural management. However, so far, no clear patterns have emerged, its effect varying in accordance with the ecological context, spatial scale, and geographic area. We aimed to assess whether the discontinuation of land cultivation and pasture grazing leads to significant changes in the abundance, diversity, and composition of small mammal communities. These were surveyed in transects of live traps set in used and abandoned arable fields and pastures in highly patched agricultural landscapes in Transylvania (Romania). Farmland abandonment was positively related to species richness, taxonomic and functional diversity, and abundance. Its effect was stronger in pastures, where intensive grazing is a limiting factor for small mammals. Functional trait composition was also sensitive to fallowing and abandonment of grazing, which promote diurnal activity, broader niches, and lower fertility. In conclusion, small mammals benefit from the maintenance of uncultivated plots and low numbers of grazing livestock, which we recommend as management strategy in traditional mosaic landscapes, to support taxonomic and functional biodiversity with implications in ecosystem service functionality. Our results also revealed more diverse communities than those showcased by similar studies in central and western Europe, with similar overall abundances.